Compact Operators for Almost Conservative and Strongly Conservative Matrices. (24th March 2014) - Mohiuddine, S. A.; Mursaleen, M.; Alotaibi, A.
Abstract : We obtain the necessary and sufficient conditions for an almost conservative matrix to define a compact operator. We also establish some necessary and sufficient (or only sufficient) conditions for operators to be compact for matrix classes ( f, X ), where X = c, c 0, l ∞ . These results are achieved by applying the Hausdorff measure of noncompactness.